A constitutive structural parameter cb for the work hardening behavior of additively manufactured Ti‐6Al‐4V. Issue 5 (3rd August 2021) - Jankowski, Alan F.
Abstract: The mechanical behavior of Ti‐6Al‐4V produced by additive manufacturing processes is assessed as based on a model derived from the Kocks–Mecking relationship. A constitutive parameter cb is derived from a linear Kocks–Mecking relationship for the microstructure that is characteristic of the work hardening behavior. The formulation for cb is determined by considering the plastic strain between the strengths at the proportional limit and the plastic instability. In this way, the model accommodates the variation in work hardening behavior observed when evaluating material as produced and tested along different orientations. The modeling approach is presented and evaluated for the case of Ti‐6Al‐4V additively manufactured materials as tested under quasi‐static uniaxial tension. It is found that different test specimen orientations, along with postbuild heat treatments, produce a change in the microstructure and plasticity behavior which can be accounted for in the corresponding change of the cb values.